MOSFET-Based Voltage Reference Circuits in the Last Decade: A Review - Elisabetta Moisello; Edoardo Bonizzoni; Piero Malcovati (Micromachines)
Voltage reference circuits are a basic building block in most integrated microsystems, covering a wide spectrum of applications. Hence, they constitute a subject of great interest for the entire microelectronics community. MOSFET-based solutions, in particular, have emerged as the implementation of choice for realizing voltage reference circuits, given the supply voltage scaling and the ever-lower power consumption specifications in various applications. For these reasons, this paper aims to review MOSFET-based voltage reference circuits, illustrating their principles of operation, as well as presenting a detailed overview of the state-of-the-art, in order to paint an accurate picture of the encountered challenges and proposed solutions found in the field in the last decade, thus providing a starting point for future research in the field.